The Role of Social Environment In Shaping Students' Decisions To Do FNB Business - Hamdani, Nizar Alam; Safari, Shabina Meisya Andriani; Dahlena, Alni; Maulani, Galih Abdul Fatah; Adiansyah, Adi; Isnawati, Isnawati (Entrepreneurship Faculty, Universitas Garut, 2024)
The crucial role of the environment in determining business opportunities, especially in the context of micro, small, and medium enterprises (MSMEs). Business development in this modern era does not only depend on internal strength, but also on the ability to adapt and innovate with the environment. The purpose of this study is to identify how perceptions of security in the surrounding environment influence community engagement and social cohesion. The research method used is a case study in qualitative research, data collection techniques using observation, interviews and documentation studies through data triangulation, data analysis techniques using reduction, data presentation, verification and conclusions. The research results identified that a positive social environment can encourage students to take the risks necessary to start and develop their businesses. Therefore, the role of the social environment in forming the FnB business is greatly influenced by the potential and opportunities in the environment, this can encourage the formation of students' abilities in seeing opportunities in the environment.